The effects of facial expression and relaxation cues on movement economy, physiological, and perceptual responses during running. (January 2018) - Brick, Noel E.; McElhinney, Megan J.; Metcalfe, Richard S.
Abstract: Objectives: Previous research has supported the beneficial effects of relaxation training on running economy. However, no studies have compared the effects of brief contact instructions to alter facial expression or to relax on running economy or running performance. The primary aim of this study was to determine the effect of such attentional instructions on movement economy, physiological, and perceptual responses during running. Method: Using a repeated measures design, 24 trained runners completed four 6 min running blocks at 70% of velocity at VO2max with 2 min rest between blocks. Condition order was randomized. Participants completed running blocks while smiling, frowning, consciously relaxing their hands and upper-body, or with a normal attentional focus (control). Cardiorespiratory responses were recorded continuously and participants reported perceived effort, affective valence, and activation after each condition. Results: Oxygen consumption was lower during smiling than frowning ( d  = −0.23) and control ( d  = −0.19) conditions. Fourteen participants were most economical when smiling in contrast with only one participant when consciously relaxing. Perceived effort was higher during frowning than smiling ( d  = 0.58) and relaxing ( d  = 0.49). Activation was higher during frowning than all other conditions (all d  ≥ 0.59). Heart rate, affective valence, and manipulation adherence did not differ between conditions. Conclusion: Periodic smiling may improve movement economy during vigorous intensity running. In contrast, frowning may increase both effort perception and activation. A conscious focus on relaxing was not more efficacious on any outcome. The findings have implications for applied practice to improve endurance performance. Highlights: Investigated the effects of smiling, frowning, and relaxation during running. Outcome measures included running economy, perceived effort, and affective state. Smiling improved running economy in comparison with frowning and a control trial. Perceived effort was higher when frowning in comparison with smiling and relaxing. Periodic smiling may be an effective attentional cue to enhance running performance.